1999
DOI: 10.2196/jmir.1.suppl1.e127
|View full text |Cite
|
Sign up to set email alerts
|

UST1/435: HON's Fourth Survey on the Usage of the Internet for Medical and Health Internet Purposes

Abstract: IntroductionTo remain competitive, the providers of medical and health-related information must continually adapt their Web sites to new market demands and trends. Successful adaptation depends, among other things, on understanding users' needs. The Health on the Net Foundation (HON) has been conducting regular surveys of user-traffic since 1997. The fourth and latest in the series, conducted through the months of March and April, 1999, obtained 4,437 responses, compared to 1,863 responses obtained by the thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…General trends from the Health On the Net Foundation surveys have found that the usefulness of the web is increasing. Ninety-eight per cent of respondents to the most recent survey agreed with the statement 'I have found useful medical/health information on the Internet', compared with 93% and 95% in previous surveys (Boyer et al 1998, Health On the Net Foundation 1999a, 1999b. Of the health professionals' responses, 68.5% reported that their patients discussed health information found on the web with them (Health On the Net Foundation 2000).…”
Section: Why Should the World Wide Web Be Used In Patient Education?mentioning
confidence: 75%
“…General trends from the Health On the Net Foundation surveys have found that the usefulness of the web is increasing. Ninety-eight per cent of respondents to the most recent survey agreed with the statement 'I have found useful medical/health information on the Internet', compared with 93% and 95% in previous surveys (Boyer et al 1998, Health On the Net Foundation 1999a, 1999b. Of the health professionals' responses, 68.5% reported that their patients discussed health information found on the web with them (Health On the Net Foundation 2000).…”
Section: Why Should the World Wide Web Be Used In Patient Education?mentioning
confidence: 75%
“…E-medicine involves the ability to synergize all stages in the medical processes such as surgery, diagnosis, in-patient and outpatient care into a single e-medicine platform such that doctors and other medical professionals collaborate and share data via a one-stopshop platform for multiple services on a network [19]. The relative advantage of e-medicine is that it enables doctors and other medical staff, patients to access their medical information needs either online or via emails or other online communities [20,21].…”
Section: Introductionmentioning
confidence: 99%